Drawing Lines in the Museum: Plains Cree Ontology as Political Practice - Poirier, Claire (Anthropologica, 2022)
This article examines how a Plains Cree elder "devel- ops protocol" with an extensive collection of Plains Cree sacred materials. Protocols- both political and ceremonial acts that govern through laws of exchange and reciprocity - involve humans and the sacred items in a relational system of agents. Taking Glenbow Museum's storage room as a meeting place for two distinct ontological engagements - the state via museolog- ical practice, and the Cree through the protocols of one elder - conflicts in how each approaches sacred subject matter are iden- tified. While the state assumes bureaucracy must prevail, the Cree elder requires protocols to guide the process.